Optimizing the formation of the acquired enamel pellicle in vitro for proteomic analysis - Vinícius Taioqui PELÁ; Talita Mendes Oliveira VENTURA; Marília Afonso Rabelo BUZALAF (University of São Paulo, 2020)
Abstract Saliva is the major contributor for the protein composition of the acquired enamel pellicle (AEP), a bacteria-free organic layer formed by the selective adsorption of salivary proteins on the surface of the enamel. However, the amount of proteins that can be recovered is even smaller under in vitro condition, due to the absence of continuous salivary flow. Objective This study developed an in vitro AEP protocol for proteomics analysis using a new formation technique with different collection solutions. Methodology 432 bovine enamel specimens were prepared (4x4 mm) and divided into four groups (n=108). Unstimulated saliva was provided by nine subjects. The new AEP formation technique was based on saliva resupply by a new one every 30 min within 120 minutes at 37ºC under agitation. AEP was collected using an electrode filter paper soaked in the collection solutions according with the group: 1) 3% citric acid (CA); 2) 0.5% sodium dodecyl sulfate (SDS); 3) CA followed by SDS (CA+SDS); 4) SDS followed by CA (SDS+CA). The pellicles collected were processed for analysis through LC-ESI-MS/MS technique. Results A total of 55 proteins were identified. The total numbers of proteins identified in each group were 40, 21, 28 and 41 for the groups CA, SDS, CA+SDS and SDS+CA, respectively. Twenty-three typical AEP proteins were identified in all groups, but Mucin was only found in CA and CA+SDS, while three types of PRP were not found in the SDS group. Moreover, a typical enamel protein, Enamelin, was identified in the CA+SDS group only. Conclusion The new technique of the in vitro AEP formation through saliva replacement was essential for a higher number of the proteins identified. In addition, considering practicality, quantity and quality of identified proteins, citric acid seems to be the best solution to be used for collection of AEP proteins.